An updated Catalogue of Cossoidea (Lepidoptera) from India - Ahmad, Jalil; Joshi, Rahul; Singh, Navneet (Zootaxa, 2023)
We catalogue 165 species in 81 genera representing six families of Cossoidea present in India. Sesiidae is the most dominant family in India, consisting 89 species in 38 genera, followed by Cossidae with 47 species in 28 genera, Brachodidae with 13 species in six genera, Metarbelidae with 12 species in seven genera, Ratardidae with three species in single genus and the Dudgeoneidae is known by single species. A comprehensive data on the species diversity of all the families of Indian Cossoidea, with information on type species, type locality, synonyms, clarifications, and distribution in different parts of India and Globe, are provided.